Women's struggle in patriarchal society: Relation of gender, social, and economy in Niswah al-Sūq al-'Atīq by Majid Sulaiman - Yuandika Putri; Ulil Abshar (Jurusan Bahasa dan Sastra Arab Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2025)
In contemporary Arabic literature, gender inequality and patriarchal structures remain underexplored in works written by men. While numerous studies have examined feminist themes in Arabic novels, few have investigated how male authors portray women's social positions through a sociological perspective. This study examines how Majid Sulaiman's Niswah al-Sūq al-’Atīq reflects patriarchal oppression and social realities in Arab society, utilizing Ian Watt's sociological framework of literature. This study employs qualitative descriptive methods through desk research, analyzing the novel's representation of socio-cultural realities, social structures, and gender dynamics. Niswah al-Sūq al-’Atīq serves as a data source and is analyzed using Watt's framework, which examines three dimensions: the author's social context, literature as a reflection of society, and the social function of literary works. This study analyzes key quotes from the novel, supported by news sources documenting similar cases. The research findings reveal that the female characters in Niswah al-Sūq al-’Atīq embody three interrelated dimensions of patriarchal oppression: economic inequality that traps families in a cycle of debt, gender norms that limit women's mobility and autonomy, and complex social relations in which the market simultaneously reinforces class hierarchies while enabling women's solidarity and resistance. These findings suggest that literature functions as a critical cultural document capable of exposing and challenging gender inequalities in the Middle Eastern context. This study contributes to gender-sensitive readings of Arabic fiction by demonstrating that Western literary sociological frameworks remain analytically productive when recontextualized in non-Western cultural contexts, while revealing how women exercise agency and resistance within patriarchal constraints.